Optimalization of strategic management to enhancing CEO’s transformational leadership - Puspito, Hendro; Suhariadi, Fendy (Technium Social Sciences Journal, 2024)
Globalization poses a challenge to the international community due to its infinite scope. The fourth industrial revolution, often known as Industrial Revolution 4.0, is either already underway or is coming quickly. In this revolution, previously unheard-of levels of connectedness and communication are made possible by the integration of industrial equipment with the internet and information and communication technology (ICT). Building a cohesive team was a key priority for transformational leaders to effect positive change. They would encourage improvements for both their staff and the system. Transformational leaders support employees' performance improvement to attain a professional level by rewarding them, whereas transactional leaders reward the company's profits. The purpose of this research was to determine how best to use strategic management to support the transformational leadership of the CEO. This study combined a literature study methodology with a qualitative approach. The study's findings indicated that, in order for a leader to practice transformational leadership, they must build a stronger bond with their followers. Through an applicable strategic management process, leaders must enable followers to see their interests as being more significant than their own to further the goals and objectives of the group or organization. best possible.